2018
DOI: 10.18632/oncotarget.25523
|View full text |Cite
|
Sign up to set email alerts
|

FOXP3 and miR-155 cooperate to control the invasive potential of human breast cancer cells by down regulating ZEB2 independently of ZEB1

Abstract: Control of oncogenes, including ZEB1 and ZEB2, is a major checkpoint for preventing cancer, and loss of this control contributes to many cancers, including breast cancer. Thus tumour suppressors, such as FOXP3, which is mutated or lost in many cancer tissues, play an important role in maintaining normal tissue homeostasis. Here we show for the first time that ZEB2 is selectively down regulated by FOXP3 and also by the FOXP3 induced microRNA, miR-155. Interestingly, neither FOXP3 nor miR-155 directly altered th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 63 publications
0
16
0
Order By: Relevance
“…MiR-155 plays crucial roles in the immune response, tumorigenesis and stem cell differentiation [33][34][35][36] and has been reported to target and repress many genes including SOCS1, TNF-α, and SHIP1 [18][19][20]. Dudda et al reported that miR-155 and its target gene, SOCS1, are key regulators of effector CD8( +) T cells as they affect cytokine signaling through STAT5 [37].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-155 plays crucial roles in the immune response, tumorigenesis and stem cell differentiation [33][34][35][36] and has been reported to target and repress many genes including SOCS1, TNF-α, and SHIP1 [18][19][20]. Dudda et al reported that miR-155 and its target gene, SOCS1, are key regulators of effector CD8( +) T cells as they affect cytokine signaling through STAT5 [37].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ZEB2 plays a synergistic effect with cdc42 GTPase-activating protein, as a novel E-cadherin transcriptional repressor, to facilitate breast cancer tumor growth and metastasis to lung [40]. Previous studies also uncover that ZEB2 can be regulated by miRNAs, including miR-29b, miR-30a, miR-155, miR-204 and miR-205, in the development of breast cancer aggressiveness [26,27,39,41,42]. In the present study, our findings extended the role of ZEB2, as an oncogene promotion of cell proliferation in breast cancer, that was a direct target of miR-653.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies also reveal that ZEB2 contributes to breast cancer progression by coordinating EMT [24,25]. Post-transcriptional regulatory mechanism has been shown that miR-30a, miR-155 and miR-200 family members inhibit human breast cancer cells invasion by down-regulating ZEB2 [26,27]. However, the association between circRNA and ZEB2 in the pathogenesis of breast cancer is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…SATB1 interactions with transcription activators and repressors are determined by its post-transcriptional modifications like phosphorylation or acetylation [22,23]. It was shown that STAB1 can also be regulated by numerous microRNAs, including miR-191, miR-155, miR-448, miR-7, miR-302a-3p and miR-21-5p [24,25,26,27,28,29,30]. SATB1 regulates gene expression on a tissue-specific manner—it binds to distinct genomic regions and regulates different sets of genes depending on the cell type [31].…”
Section: Introductionmentioning
confidence: 99%